Pengaruh Brand Awareness, Brand Image dan Media Communication terhadap Minat Nasabah Memilih BSI Griya Hasanah di BSI KCP Garut Kadungora - Aminah Jamaliah, Alya Siti; Rakhman, Faisal (Jurnal Dimamu, 2024)
Based on observation results, that the background of this research is the tendency for a decrease in BSI Griya Hasanah customers at BSI KCP Garut Kadungora over the past three years. This is caused by the lack of Brand Awareness, Brand Image and Media Communication at BSI KCP Garut Kadungora, which affects customer interest in choosing BSI Griya Hasanah at the bank. This study aims to find out how Brand Awareness, Brand Image and Media Communication influence the interest in choosing BSI Griya Hasanah products, both partially and simultaneously at BSI KCP Garut Kadungora. The research object is BSI Griya Hasanah customers. The type of research is associative quantitative with primary data types and uses data collection techniques in the form of observation, interviews, literature study, and questionnaires. While the sampling technique is non-probability sampling with purposive sampling. The population is all BSI Griya Hasanah customers at BSI KCP Garut Kadungora, totaling 72 people with a sample of 61 people. The results showed that there was a significant influence between brand awareness on customer interest in BSI Griya Hasanah of 59,2% where the value of t count > t table (9,251 > 2,001), there was a significant influence between brand image on the interest of BSI Griya Hasanah customers by 59,9% with the results of the t test where t count > t table (9,378 > 2,001), there is a significant effect between media communication on customer interest BSI Griya Hasanah of 43,6% with the t test results where t count > t table (6,758 > 2,001), and simultaneously there is a significant influence between brand awareness, brand image and media communication on interest in choosing BSI Griya Hasanah products of 68,5% for R2 with F test results where f count > f table (41,229 > 2,76).